The Values of Sports Culture in Some Members of the Teaching at the University of Anbar - Hamid, Nabhan (Journal of Physical Education, 2010)
The research aims to: - To identify the values of culture, sports and identified by some members of the teaching at the University of Anbar and its role in the social development of individuals. And the imposition of search: - The existence of considerable variation in the possession of the values of the sports culture among the research sample. Researcher used the descriptive approach to the appropriateness of the manner of the survey and the nature of the research included a sample of search (53) of the members of the teaching in the College of Computer and the College of Education at the University of Anbar, where the research was the distribution of questionnaires containing a number of terms that measure the values of culture, sports and were collected and processed statistically. The researcher concluded the following: 1 - The value of the sports culture on the development of the dynamic qualities and skills to the highest values followed by the development of physical attributes such as strength and speed, then the values of maintaining health, then the values of recreation and equally self-testing, as well as physical abilities and mobility. 2 - The words that do not fit the values of physical culture to the members of the research and sample rates are very high. Then the researcher recommended the following: - The need to provide equipment and supplies for the practice of sports activities for the members of the teaching at the University of Anbar, and the provision of classrooms and playgrounds to suit the orientation towards the practice and demonstrated by the high ratios. - Organization of activities and sports competitions for the various members of the teaching staff and involvement of non-participation is limited to only students or members of the teaching staff of the College of Physical Education, and the inclusion of other Colleges such as College of the computer, education, engineering, law and others